Interior “KOLASE” Creative Hub sebagai Upaya Pengembangan Ekonomi Kreatif di Surabaya - Anette Firmawan Panghegar; Laksmi Kusuma Wardani; M. Taufan Rizqy (Intra, 2018)
As the second largest city in Indonesia, economic development in Surabaya is well supported by creative industry sector which also became the backbone of the economy in Surabaya. The growth of creative industry is directly proportional to the emergence of creative young generation in Surabaya. Designing a creative hub is a form of response to the magnitude of potential creative resources of creative young generation Surabaya on the development of creative economy. This creative hub will be designed to create a platform for young people in Surabaya, especially the creators, innovators, local entrepreneurs, makers, and all other creative people to meet, interact, collaborate, and innovate. The concept of this design is to provide public facilities that can accommodate the positive activities of young people and create an ecosystem that is conducive to the development of creative economy in Surabaya. Therefore, the design scope includes creative office, event space, fabrication workshop, and café.